Novel Applications of Microwave Techniques in the Food and Environmental Industries - László, Zsuzsanna; Simon, Erika; Hodúr, Cecilia; Fenyvessy, József (Acta Agraria Debreceniensis, 2005)
During the microwave processing, despite the conventional heating, the material heats consistently inside. This property of microwave is utilized by drying and dehydration processes. The thermal sensitivity of raw materials of food industry requires development of gentle, fast and controllable technologies, which is realizable by means of combination of conventional and microwave techniques. The other important application area of the microwave technique is food industrial practice is enhancing the microbial safety of products, mainly by pasteurization processes. In recent time the strict environmental regulation necessitate developing more effective treatment of wastes, waste waters and sewage sludge. Because a part of these techniques are heat and power demanded, the microwave technique may be an alternative process in execution of sludge conditioning, drying or gasification and pyrolysis.